Biallelic variants in RNU12 cause CDAGS syndrome. Issue 8 (15th June 2021) - Xing, Chao; Kanchwala, Mohammed; Rios, Jonathan J.; Hyatt, Tommy; Wang, Richard C.; Tran, An; Dougherty, Irene; Tovar‐Garza, Andrea; Purnadi, Christy; Kumar, Monique G.; Berk, David; Shinawi, Marwan; et al.
Abstract: CDAGS Syndrome is a rare congenital disorder characterized by Craniosynostosis, Delayed closure of the fontanelles, cranial defects, clavicular hypoplasia, Anal and Genitourinary malformations, and Skin manifestations. We performed whole exome and Sanger sequencing to identify the underlying molecular cause in five patients with CDAGS syndrome from four distinct families. Whole exome sequencing revealed biallelic rare variants that disrupt highly conserved nucleotides within the RNU12 gene. RNU12 encodes a small nuclear RNA that is a component of the minor spliceosome and is essential for minor intron splicing. Targeted sequencing confirmed allele segregation within the four families. All five patients shared the same rare mutation NC_000022.10:g.43011402C>T, which alters a highly conserved nucleotide within the precursor U12 snRNA 3ʹ extension. Each of them also carried a rare variant on the other allele that either disrupts the secondary structure or the Sm binding site of the RNU12 snRNA. Whole transcriptome sequencing analysis of lymphoblastoid cells identified 120 differentially expressed genes, and differential alternative splicing analysis indicated there was an enrichment of alternative splicing events in the patient. These findings provide evidence of the involvement of RNU12 in craniosynostosis, anal and genitourinary patterning, and cutaneous disease.